Characterizing Protection Effects on Network Epidemics driven by Random Walks - Souza, Ronald; Figueiredo, Daniel (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance), 2020)
Protection effects (PFx) denote protective measures taken by individuals (such as to wear masks and wash hands) upon their risk-perception towards an ongoing epidemic outbreak. The holistic force produced may fundamentally change the course of a spreading, with respect to both its reach and duration. This work proposes a model for PFx on network epidemics where nodes are sites mobile-agents may visit. Risk aversion is encoded as random-walks biased to safe sites. Assuming the network is a complete graph, the model is analyzed and framed as a classical SIS. We find a regime under which PFx preclude endemic steady-states upon arbitrarily large rates for both walk and transmissibility. Simulation results support our theoretical findings.